Case Report: Obstructive sleep apnea syndrome-associated blood pressure fluctuations combined with simultaneous central retinal vein and artery occlusion - Gu, Zhenzhen; Luo, Jinhua; Chen, Xi; Chen, Kaiming; Ju, Pin; Sun, Mei; Hao, Xiaofeng; Xie, Like (Frontiers in Medicine, 2025)
BackgroundCentral retinal vein occlusion (CRVO) and central retinal artery occlusion (CRAO) are serious eye blood vessel problems usually linked to heart health issues. In this case study, a patient with a diagnosis of obstructive sleep apnea syndrome (OSAS) but no traditional thrombotic or atherosclerotic risk factors experienced a rare co-occurrence of CRVO and CRAO.Case presentationA formerly healthy 42-year-old man came with dark shadows in his right eye and acute-onset blurred vision. A thorough ophthalmic exam verified simultaneous CRVO and CRAO. Later, polysomnography showed moderate hypoxemia and severe OSAS. The patient received integrated traditional Chinese medicine, perfusion enhancement, and intraocular pressure lowering as part of multimodal therapy. With notable retinal edema resolution, post-treatment visual acuity returned to 20/20.ConclusionEspecially in patients without conventional cardiovascular risks, this case implies that OSAS might be a separate risk factor for combined CRVO and CRAO. Intermittent hypoxia, sympathetic overactivity, and hypercoagulability are probably among the underlying mechanisms. Optimizing management plans in idiopathic retinal vascular occlusions seems to depend on early OSAS screening. Moreover, this case shows the possible therapeutic benefit of combining pharmacological and conventional treatments for complicated ocular vascular disorders.